Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Apparel Under Armour di Jakarta - Haryadi, Andrian; Ruhana Dara, Siti (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
This research aims to analyze the effect of product quality and price on purchasing decisions for Under Armour brand apparel for consumers. This study uses a quantitative approach using a research instrument in the form of a questionnaire which is distributed to 260 respondents. Based on the results of the research carried out, the findings were that product quality has a significant effect on purchasing decisions for Under Armour apparel. The price variable has a significant influence on purchasing decisions. Product quality variables and price variables together have a significant effect on purchasing decisions.